Targeting Mitochondrial Oncometabolites: A New Approach to Overcome Drug Resistance in Cancer - Martina Godel; Giacomo Ortone; Dario Pasquale Anobile; Martina Pasino; Giulio Randazzo; Chiara Riganti; Joanna Kopecka (Pharmaceutics, 2021)
Drug resistance is the main obstacle for a successful cancer therapy. There are many mechanisms by which cancers avoid drug-mediated death, including alterations in cellular metabolism and apoptotic programs. Mitochondria represent the cell’s powerhouse and the connection between carbohydrate, lipid and proteins metabolism, as well as crucial controllers of apoptosis, playing an important role not only in tumor growth and progression, but also in drug response. Alterations in tricarboxylic acid cycle (TCA) caused by mutations in three TCA enzymes—isocitrate dehydrogenase, succinate dehydrogenase and fumarate hydratase—lead to the accumulation of 2-hydroxyglutarate, succinate and fumarate respectively, collectively known as oncometabolites. Oncometabolites have pleiotropic effects on cancer biology. For instance, they generate a pseudohypoxic phenotype and induce epigenetic changes, two factors that may promote cancer drug resistance leading to disease progression and poor therapy outcome. This review sums up the most recent findings about the role of TCA-derived oncometabolites in cancer aggressiveness and drug resistance, highlighting possible pharmacological strategies targeting oncometabolites production in order to improve the efficacy of cancer treatment.